4(h+2)-2h=3(2+h)

Simple and best practice solution for 4(h+2)-2h=3(2+h) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(h+2)-2h=3(2+h) equation:



4(h+2)-2h=3(2+h)
We move all terms to the left:
4(h+2)-2h-(3(2+h))=0
We add all the numbers together, and all the variables
4(h+2)-2h-(3(h+2))=0
We add all the numbers together, and all the variables
-2h+4(h+2)-(3(h+2))=0
We multiply parentheses
-2h+4h-(3(h+2))+8=0
We calculate terms in parentheses: -(3(h+2)), so:
3(h+2)
We multiply parentheses
3h+6
Back to the equation:
-(3h+6)
We add all the numbers together, and all the variables
2h-(3h+6)+8=0
We get rid of parentheses
2h-3h-6+8=0
We add all the numbers together, and all the variables
-1h+2=0
We move all terms containing h to the left, all other terms to the right
-h=-2
h=-2/-1
h=+2

See similar equations:

| 1/4x+3/4=x | | w/4+12=26 | | 8(-1-2x)=-5(4x+4) | | X+6/3+x+3/3=x-8 | | 4^(7x^2)=5^(7x) | | 2/3(9s-3/2)=(0.45+5)+1.2 | | −8x−5+3x=7+4x−9 | | 35=2w+17 | | 20-10x=60+6x | | 3=n+7/2 | | 1=2/k | | 6x-8=37-3x | | 12=7+7k | | X+8/6=3/2-x-1/3 | | 7x+5=98+2 | | x7+5=98+2 | | x7+5=x+98-2 | | 2000(x–24)+5000=18,000 | | 13x+4=15x | | 3-(x-6)+7=5x-8 | | 2.7=|-9p| | | -31-3k=-8(-k+8) | | 3a-5=9a | | 23-9=2d | | 0.1^x=100 | | 2x-5=-0.5x+4 | | 7/25=x/10 | | X=6y+12/6 | | 2x/7-x=×/56-5/8 | | 2(k+3)=10-5 | | 2(4+3)=2x(4+3) | | -7+z/4=3 |

Equations solver categories